Bifunctional 4,5-Diiodoimidazole Interfacial Engineering Enables Simultaneous Defect Passivation and Crystallization Control for High-Efficiency Inverted Perovskite Solar Cells - Huaxi Gao; Yu Zhang; Ihtesham Ghani; Min Xin; Danish Khan; Junyu Wang; Di Lu; Tao Cao; Wei Chen; Xin Yang; Zeguo Tang (Nanomaterials)
Despite the rapid efficiency advancement of perovskite solar cells (PSCs), non-radiative recombination at the buried interface between self-assembled monolayers (SAMs) and perovskite remains a critical bottleneck, primarily due to interfacial defects and energy level mismatch. In this study, we demonstrate a bifunctional interlayer engineering strategy by introducing 4,5-diiodoimidazole (4,5-Di-I) at the Me-4PACz/perovskite interface. This approach uniquely addresses two fundamental limitations of SAM-based interfaces: the insufficient defect passivation capability of conventional Me-4PACz due to steric hindrance effects and the poor perovskite wettability on hydrophobic SAM surfaces that exacerbates interfacial voids. The imidazole derivatives not only form strong Pb–N coordination bonds with undercoordinated Pb2+ but also modulate the surface energy of Me-4PACz, enabling the growth of pinhole-free perovskite films with preferential crystal orientation. The champion device with 4,5-Di-I modification achieves a power conversion efficiency (PCE) of 24.10%, with a VOC enhancement from 1.12 V to 1.14 V, while maintaining 91% of initial PCE after 1300 h in N₂ atmosphere (25 °C), demonstrating superior stability under ISOS-L-2 protocols. This work establishes a universal strategy for interfacial multifunctionality design, proving that simultaneous defect suppression and crystallization control can break the long-standing trade-off between efficiency and stability in solution-processed photovoltaics.